2019
DOI: 10.1155/2019/3563024
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variability of Summer Precipitation Efficiency in East Asia

Abstract: Precipitation efficiency (PE) is a crucial physical quantity in convective processes, describing the efficiency of rainfall generation from cloud detrainment. Although the importance of PE in extreme precipitation events is widely accepted, the evolution of PE in the warming climate and the associated moisture processes in East Asia are still not well understood. To address these issues, the interdecadal variability of PE in East Asia during summer in 1979–2016 is investigated in this study. Two major modes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Interesting to note, the ratio of precipitation delivered to the NWC from the STP (9.5%) and SEC (8.2%) is higher than that of water vapor (4.7% and 4.4%), while the ratio of precipitation from the NA (11.2%) and EUP (11.5%) is lower than that of water vapor (19.2% and 16.6%). Based on investigating the precipitation conversion e ciency in these regions, which is de ned as: 1 where is precipitation conversion e ciency, is surface precipitation (mm), and is the mass of water vapor in a column of air 29,30 (kg m − 2 ), we found that the precipitation conversion e ciency of the STP and SEC (southwestern air ow transport; 19.1% and 17.6%) is higher than that of the EUP and NA (northwestern air ow transport; 6.4% and 5.5%). By examining the spatial distribution of precipitation contributions from different sources to the NWC (as shown in Fig.…”
Section: Moisture Sourcesmentioning
confidence: 99%
“…Interesting to note, the ratio of precipitation delivered to the NWC from the STP (9.5%) and SEC (8.2%) is higher than that of water vapor (4.7% and 4.4%), while the ratio of precipitation from the NA (11.2%) and EUP (11.5%) is lower than that of water vapor (19.2% and 16.6%). Based on investigating the precipitation conversion e ciency in these regions, which is de ned as: 1 where is precipitation conversion e ciency, is surface precipitation (mm), and is the mass of water vapor in a column of air 29,30 (kg m − 2 ), we found that the precipitation conversion e ciency of the STP and SEC (southwestern air ow transport; 19.1% and 17.6%) is higher than that of the EUP and NA (northwestern air ow transport; 6.4% and 5.5%). By examining the spatial distribution of precipitation contributions from different sources to the NWC (as shown in Fig.…”
Section: Moisture Sourcesmentioning
confidence: 99%
“…Especially in China, which is under the control of the East Asian summer monsoon, flood season disaster events are often prone to occur in summer. Considering that ENSO also has an impact on precipitation in Eurasia [59][60][61][62], this study compares the relationship between summertime AO and East Asian precipitation for different sub-periods, with the influence of ENSO excluded (Figure 2). Considering that precipitation is influenced by multiple factors and is complex, previous studies on precipitation (e.g., [44,61,63,64]) have used a confidence level of 80% to 90%.…”
Section: Impacts Of Ao On Precipitation In East Asiamentioning
confidence: 99%
“…Extreme rainfall in SWC has obvious interannual and interdecadal variability, and its spatial distribution is uneven. Long‐term climate change, human influence, and geographical factors have had a huge impact on it (Liu et al ., 2015; Mu et al ., 2017; Wang et al ., 2019). In recent decades, human activities have aggravated soil erosion and rocky desertification in SWC, making more frequent natural hazards caused by extreme rainfall (Gao and Sang, 2017; Wei et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%